Hospitalidade e cidade: continuidades e ambivalências no uso do espaço público - WASSALL, Alice Ribeiro A. (2017)
The main objective of this work is to understand, in the light of the concept of hospitality, the relations between cities and public spaces from the point of view of its goers and residents. Two public squares located in different cities of the State of São Paulo, Campinas and São Paulo, were chosen as objects of study, which passed through very significant processes of change, but it is not intended to do a comparison between the squares. It is an exploratory research and by the methodological point of view was used observation in loco, the application of survey questionnaires to residents and goers, and content analysis of daily newspaper material that referred to the squares. In addition, the collection of information was complemented by interviews with key people who were able to clarify details of the trajectory and dynamics of each square. The results point to the importance of these spaces in the constitution of collective life in large cities and in the changes in the use of public space at different times. It is concluded that these spaces are privileged places for the understanding of the relations of hospitality in the contemporary world.